Olga MOJŽÍŠOVÁ – Tomáš BERNHARDT (eds.), Bedřich Smetana. Deníky. Diaries. I. (1840–1847), Praha, Národní muzeum 2022, 736 s. (+ 24 s. obrazové přílohy). ISBN 978-80-7036-724-7 (print), ISBN 978-80-7036-725-4 (pdf). - Jaklová, Helena (Theatrum historiae, 2023)